A New Approach to Sovereign Debt Restructuring - Krueger, Anne (Pamphlet Series, 2002)
In recent years there has been extensive discussion inside and outside the IMF on the need to develop a new approach to sovereign debt restructuring. Exploring ways to improve the sovereign debt restructuring process is a key part of the international community's efforts to strengthen the architecture of the global financial system. This pamphlet by IMF First Deputy Managing Director Anne O.Krueger draws together the latest IMF thinking on the controversial issue in a single publication.